Financial Help-Seeking Behaviors of Young Adults - Christina E. Glenn; Stuart J. Heckman (Journal of Financial Therapy, 2020)
The financial help-seeking behaviors of Millennials are explored and guided by the Family Financial Socialization conceptual model developed by Gudmunson and Danes (2011). Using data from the 1997 cohort of the National Longitudinal Study of Youth, a random effects probit model was used to estimate the probability of a respondent seeking financial advice at any point in time from 2006 to 2013. Results indicate personal and family demographic characteristics are associated with the decision to seek financial advice. Further analysis was conducted to determine the probability of seeking help from a financial professional. Among those who sought help, gender, marital status, income, education, financial knowledge, and parent education were significant predictors in the decision to seek help from a professional rather than a non-professional.
Keywords: financial help-seeking; financial socialization; Millennials